2019
DOI: 10.3390/toxins11100607
|View full text |Cite
|
Sign up to set email alerts
|

Contribution and Interaction of Shiga Toxin Genes to Escherichia coli O157:H7 Virulence

Abstract: Escherichia coli O157:H7 is the predominant cause of diarrhea-associated hemolytic uremic syndrome (HUS) worldwide. Its cardinal virulence traits are Shiga toxins, which are encoded by stx genes, the most common of which are stx1a, stx2a, and stx2c. The toxins these genes encode differ in their in vitro and experimental phenotypes, but the human population-level impact of these differences is poorly understood. Using Shiga toxin-encoding bacteriophage insertion typing and real-time polymerase chain reaction, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The toxin genotypes of the O157:H7 isolates were stx 1a and stx 2a (n = 3), stx 2a (n = 1), or stx 2a and stx 2c (n = 5). Our finding that five of the strains were stx 2a +stx 2c + was not surprising to us because many O157:H7 isolates in the USA and Finland have that genotype (Eklund et al, 2002;Tarr et al, 2019), including the strain from the 2006 spinach outbreak in the USA (Uhlich et al, 2008). Of the nine known loci in which stx phages insert into the host bacterial chromosome (Bonanno et al, 2015), we observed that for strains lysogenized by both stx 1a -and stx 2a -phages, the stx 1a phage occupied yehV, and the stx 2 -phage occupied wrbA.…”
Section: Stx Subtypes Stx-phage Insertion Site and Virulence Gene Pmentioning
confidence: 56%
“…The toxin genotypes of the O157:H7 isolates were stx 1a and stx 2a (n = 3), stx 2a (n = 1), or stx 2a and stx 2c (n = 5). Our finding that five of the strains were stx 2a +stx 2c + was not surprising to us because many O157:H7 isolates in the USA and Finland have that genotype (Eklund et al, 2002;Tarr et al, 2019), including the strain from the 2006 spinach outbreak in the USA (Uhlich et al, 2008). Of the nine known loci in which stx phages insert into the host bacterial chromosome (Bonanno et al, 2015), we observed that for strains lysogenized by both stx 1a -and stx 2a -phages, the stx 1a phage occupied yehV, and the stx 2 -phage occupied wrbA.…”
Section: Stx Subtypes Stx-phage Insertion Site and Virulence Gene Pmentioning
confidence: 56%
“…This reduction in Stx2a toxicity is potentially due to the stronger receptor binding affinity to the globotriaosylceramide (Gb3) receptor of the B subunit of Stx1a, blocking out the binding of Stx2a to the Gb3 receptor (Head et al, 1991;Tesh et al, 1993;Zumbrun et al, 2010;Karve and Weiss, 2014;Russo et al, 2014;Cherubin et al, 2019). The reduced toxicity of Stx2a in the presence of Stx1a has also been linked epidemiologically, reporting a reduced risk of HUS from STEC strains that possess an stx1a and stx2a genotype (Ostroff et al, 1989;Brandal et al, 2015;Tarr et al, 2019). The presence of two or more stx-encoding prophage regions expressing different subtypes of Shiga toxins may not necessarily cause an additive potential in virulence, the effects can be synergistic or antagonistic.…”
Section: Core Genome Analysismentioning
confidence: 99%
“…Recently, with the stx2a genotype as compared to the stx1a/stx2a genotype, two of the most common genotypes in USA and Japan (34,35,36). Tarr et al (33) also found that the virulence of the stx2a/stx2c genotype, predominant in other settings (37,38), was similar to stx2a-only genotype.…”
Section: Methodsmentioning
confidence: 89%